Outcomes in older kidney recipients from older donors: A propensity score analysis - Cuadrado-Payán, Elena; Montagud-Marrahi, Enrique; Casals-Urquiza, Joaquim; del Risco-Zevallos, Jimena; Rodríguez-Espinosa, Diana; Cacho, Judit; Arana, Carolt; Cucchiari, David; Ventura-Aguiar, Pedro; Revuelta, Ignacio; Piñeiro, Gaston J.; Esforzado, Nuria; et al. (Frontiers in Nephrology, 2022)
Background The age of patients referred for kidney transplantation has increased progressively. However, the precise influence of age on transplant outcomes is controversial. Methods Etrospective study in which graft and recipient survival were assessed in a cohort of ≥75 years old kidney recipients and compared with a contemporary younger one aged 60-65 years through a propensity score analysis. Results We included 106 recipients between 60-65 and 57 patients of ≥75 years old with a median follow-up of 31 [13-54] months. Unadjusted one- and five-year recipient survival did not significantly differ between the older (91% and 74%) and the younger group (95% and 82%, P=0.06). In the IPTW weighted Cox regression analysis, recipient age was not associated with an increased risk of death (HR 1.88 95%CI [0.81-4.37], P=0.14). Unadjusted one- and five-year death-censored graft survival did not significantly differ between both groups (96% and 83% for the older and 99% and 89% for the younger group, respectively, P=0.08). After IPTW weighted Cox Regression analysis, recipient age ≥75 years was no associated with an increased risk of graft loss (HR 1.95, 95%CI [0.65-5.82], P=0.23). Conclusions These results suggest that recipient age should not be considered itself as an absolute contraindication for kidney transplant